2022
DOI: 10.1002/jsfa.11877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan/starch aldehyde‐catechin conjugate composite coating on the quality and shelf life of fresh pork loins

Abstract: BACKGROUND: Fresh pork is susceptible to oxidation and spoilage. Edible coating containing antioxidant and antimicrobial agents can create moisture and oxygen barriers around pork and inhibit oxidation and microbial growth in the pork. In this study, chitosan in combination with starch aldehyde-catechin conjugate (SACC) was used as a novel edible coating material for preserving fresh pork loins at chilled storage (4 ± 1 °C) for 14 days. Effect of chitosan/SACC composite coating on the quality of pork loins inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 53 publications
(231 reference statements)
1
2
0
Order By: Relevance
“…The means of 16 and 22 meq/kg were reported for treated and control samples on the 15th day, respectively. A favourable impact was also reported by Hu et al (2022) on the lipid stability of loins of pork coated with chitosan containing a starch aldehyde-catechin conjugate during two weeks of storage in a refrigerator. Markedly lower means were found for TBARS for coated pork from days 2 to 14.…”
Section: Meat and Meat Productssupporting
confidence: 55%
See 1 more Smart Citation
“…The means of 16 and 22 meq/kg were reported for treated and control samples on the 15th day, respectively. A favourable impact was also reported by Hu et al (2022) on the lipid stability of loins of pork coated with chitosan containing a starch aldehyde-catechin conjugate during two weeks of storage in a refrigerator. Markedly lower means were found for TBARS for coated pork from days 2 to 14.…”
Section: Meat and Meat Productssupporting
confidence: 55%
“…The values for TBARS on day 8 for uncoated and coated chicken were 1.98 and 0.91 mg MDA/kg, respectively Yıldırım-Yalçın et al (2021) The film contained montmorillonite (0.1%), carboxymethyl cellulose (1%, w/v), chitosan (2% w/v, in 1% acetic acid solution), tween 80 (0.25 ml/100 ml) and glycerol (0.75 ml/g) as a plasticizer The bioactive agents used were Ficuscarica extract (1.0%) and Ziziphora clinopodioides essential oil (ZCEO, 0.5, 1.0 and 2.0%) together or ZCEO alone The nanocomposite chitosan and carboxymethylcellulose films were used to wrap the fresh camel meat ( Semimembranosus ) mince and kept at 4 °C for 14 days The TBARS and peroxide values lowered significantly for the camel meat wrapped within the developed films from days 2 to 14 Khezrian and Shahbazi (2018) Lecithin: cholesterol (60:0, 50:10, 40:20, and 30:30) in dichloromethane/methanol (1:1) and 60 mg Satureja khuzestanica essential oil were used to prepare nanoliposomes. The coating solution was prepared using nanoliposomes (50:10, 1% v/v), glycerol (25%, w/w) and 2% (w/v) chitosan (in 1% acetic acid) Nanoliposomes were developed using Satureja khuzestanica The coated meat steaks from fresh lamb leg were kept at 4 °C for 20 days The TBARS values lowered significantly for the coated steaks from days 1 to 20 Pabast et al (2018) The film contained cellulose nanofibers (7.5%, w/w), glycerol (6%, w/v), and whey protein isolates (10% w/v) The bioactive agents used were rosemary oil (2%, w/v) and TiO 2 particles (1% w/w) The nanocomposite films were applied to Lamb samples from Semimembranosus and were kept at 4 °C for 15 days Significantly lower TBARS, FFA and peroxide values were recorded for the lamb wrapped within nanocomposite films from days 3 to 15 in comparison to the lamb stored within polyethylene bags Alizadeh-Sani et al (2020) The film contained starch aldehyde-catechin conjugate (0.06 g) and chitosan solution (20 g/l, in acetic acid) A conjugate developed using starch aldehyde and catechins was used as a bioactive agent The coated fresh pork loins were kept at 4 °C for 14 days The TBARS values lowered significantly for the coated pork from days 2 to 14 in comparison to uncoated pork Hu et al (2022) The film contained chitosan (1%) and gelatine (3%) Grape seed extract (0.5%) and nisin (0.1%) The coated fresh pork loins were kept at 4 °C for 20 days The TBARS values lowered significantly for the coated pork from days 5 to 20 in comparison to uncoated pork Xiong, Chen, et al (2020) The film contained tween 80 (20% dry matter), thyme essential oil, polyvinyl alcohol (Pva, 5%), curdlan (4:1 = Pva:curdlan), and glycerin (20% of dry matter) …”
Section: Meat and Meat Productsmentioning
confidence: 99%
“…Du et al [ 81 ] also demonstrated that CS−based film incorporating with rosemary extract displayed inhibitory effects on the lipid oxidation in grass carp samples. Hu et al [ 82 ] revealed a reduction in the TBARS value changes in pork meats wrapped with the CS/starch aldehyde−catechin composite film.…”
Section: Resultsmentioning
confidence: 99%